2022
DOI: 10.1002/vetr.1578
|View full text |Cite
|
Sign up to set email alerts
|

To scan or not to scan? Efficacy of transthoracic ultrasonography for ovine pulmonary adenocarcinoma screening in a large commercial UK sheep flock

Abstract: Background Transthoracic ultrasonography (TTUS) is currently the only widely used method to diagnose preclinical or subclinical ovine pulmonary adenocarcinoma (OPA) in the live sheep. However, little is known about the test characteristics of TTUS. Methods One thousand and seventy‐four breeding ewes in a flock with evidence of low OPA prevalence underwent TTUS by an experienced operator. Fifty‐one sheep were diagnosed with OPA and underwent gross postmortem examination (PME). Results Lesions consistent with OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The results of Davies and colleagues' study are not supportive of transthoracic ultrasonography being used as a screening tool for OPA in low-prevalence populations, with a relatively low proportion of animals with significant abnormalities detected on the scan being confirmed as having OPA at postmortem examination and over 40 per cent of animals identified as OPA-positive ultrasonographically having no detectable lesions at postmortem examination. 14 This contrasts with the very high sensitivity and specificity previously reported by Cousens and Scott. 12 However, in Cousens and Scott's study, the animals scanned were all thin, and many came from flocks with a confirmed history of OPA.…”
Section: What You Need To Knowmentioning
confidence: 73%
See 2 more Smart Citations
“…The results of Davies and colleagues' study are not supportive of transthoracic ultrasonography being used as a screening tool for OPA in low-prevalence populations, with a relatively low proportion of animals with significant abnormalities detected on the scan being confirmed as having OPA at postmortem examination and over 40 per cent of animals identified as OPA-positive ultrasonographically having no detectable lesions at postmortem examination. 14 This contrasts with the very high sensitivity and specificity previously reported by Cousens and Scott. 12 However, in Cousens and Scott's study, the animals scanned were all thin, and many came from flocks with a confirmed history of OPA.…”
Section: What You Need To Knowmentioning
confidence: 73%
“…In a study summarised on p 122 of this issue of Vet Record, Davies and colleagues sought to address this knowledge gap by assessing the efficacy of using transthoracic ultrasonography to screen a large flock for OPA. 14 In this study, all animals determined to have lesions consistent with OPA by the veterinary surgeon performing the scanning were sent for slaughter. A pathologist then examined the lungs, and representative sections were taken for histopathological examination.…”
Section: What You Need To Knowmentioning
confidence: 99%
See 1 more Smart Citation
“…The test performance of the TTUS technique was obtained from a previous study, 7 where 1074 breeding ewes in a flock with evidence of low OPA prevalence underwent TTUS by an experienced operator. Fifty‐one sheep were diagnosed as ‘OPA cases’ by TTUS and assigned a grade (Grade 0 = no abnormalities detected, Grade 1 = minor abnormality detected but not indicative of OPA, Grade 2 = likely OPA lesions of small to moderate size, Grade 3 = larger, more advanced lesions with the highest supposed likelihood of being OPA).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, 7 we described the performance of TTUS as a screening test in a flock with a low prevalence of disease of 1%–2%. In that study, the positive predictive value of TTUS ranged from 12% to 36%, estimated sensitivity ranged from 70% to 93% and specificity estimates ranged from 96% to 99%.…”
Section: Introductionmentioning
confidence: 99%